Adverse Pregnancy Outcome as A Result of Anaemia and Hyperglycemia with Special Focus on Time of Registration and Weight Gain During Pregnancy - Shakila Mulla; Sulabha Akarte; Ranjit Mankeshwar; Shakeel Ansari (Medsci Publications, 2014)
Introduction: Adverse pregnancy outcome is a result of many factors related to mother that may act concomitantly. Weight gain during pregnancy is one of the important tools to assess course and outcome of pregnancy. Weight gain during pregnancy is affected by many factors; the important being anaemia and hyperglycaemia. Methods: A prospective study was conducted on 400 antenatal women in rural area to assess adverse pregnancy outcome in women having anaemia, hyperglycaemia and to correlate it with weight gain and time of registration. Stata SE 10.1 was used to analyse data. Result: Mean weight gain observed was just 3.96 Kg (kilogram). Anaemia, hyperglycaemia and poor weight gain were associated with various adverse pregnancy outcomes like low birth weight, preterm delivery, Caesarian section or malpresentation. Conclusion: We need to first emphasize on adequate weight gain during pregnancy to control maternal illnesses as well as adverse pregnancy outcome.